Do Codes Make a Difference? The Case of Bank Lending and the Environment - Cowton, Christopher J. (Journal of business ethics, 2000)
Codes of conduct are a conspicuous feature of modern business organization, but doubts have been raised regarding their efficacy in ensuring high standards of behavior. Although some of the issues involved have been discussed at some length in the business ethics literature, the amount of systematic empirical evidence on the impact of codes is very limited. This paper seeks to make a contribution to that body of knowledge by studying the policies and procedures of a sample of banks which have signed a statement on banking and the environment promulgated by the United Nations Development Programme. Although some differences are found when compared with a sample of banks which did not sign the Statement, they are not extensive. The implications of the findings, for codes of conduct and for future empirical studies, are then discussed.